Maintained and Delayed Benefits of Executive Function Training and Low-Intensity Aerobic Exercise Over a 3.5-Year Period in Older Adults - Yang, Lixia (Frontiers in Aging Neuroscience, 2022)
This is a follow-up study of our previous work (Yang et al., 2020), with a specific goal to examine whether older adults are able to maintain or show delayed cognitive and psychosocial benefits of executive function training and physical exercise over a period of 3.5 years on average. Thirty-four participants from the original training study (17 from the executive function training and 17 from the aerobic exercise group) returned and completed a single follow-up session on a set of cognitive and psychosocial outcome measures. The results of the returned follow-up sample showed some significant original training transfer effects in WCST-64 performance but failed to maintain these benefits at the follow-up session. Surprisingly, episodic memory performance showed some significant improvement at the follow-up relative to baseline, signaling delayed benefits. The findings add some novel implications for cognitive training schedule and highlight the possible importance of continuous engagement in long-term cognitive enhancement in healthy older adults.